1992
DOI: 10.1080/09064709209410122
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Digestibility in Lactating Cows Fed Increasing Amounts of Protected Vegetable Oil, Fish Oil or Saturated Fat

Abstract: Fatty acid digestibility in lactating COWS fed increasing amounts of protected vegetable oil, fish oil or saturated fat. Accepted November 27, 1991. Acta Agric. Scand., Sect. A, Animal Sci. 42: 148-156, 1992. Fatty acid digestion was studied in three dairy cows cannulated in the rumen, duodenum and ileum. Cows were fed encapsulated fat sources (vegetable oil, saturated fat and fish oil). A preperiod diet was fed with no added fat. In a graeco-latin design nine diets comprising three levels of each of the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…However, the digestibility of total C16 and total C18 was similar within diet. Previous research using lactating cows with duodenal and ileal cannulae (Børsting et al 1992) found that FA digestibility of C16:0 was higher than C18:0 when dietary fat sources were encapsulated by a casein-formaldehyde process. In a review of fat digestibility studies, Lock et al (2005) found that whole-tract digestibility of C16:0 was ∼750 g kg -1 and of C18:0 was ∼720 g kg -1…”
Section: Discussionmentioning
confidence: 97%
“…However, the digestibility of total C16 and total C18 was similar within diet. Previous research using lactating cows with duodenal and ileal cannulae (Børsting et al 1992) found that FA digestibility of C16:0 was higher than C18:0 when dietary fat sources were encapsulated by a casein-formaldehyde process. In a review of fat digestibility studies, Lock et al (2005) found that whole-tract digestibility of C16:0 was ∼750 g kg -1 and of C18:0 was ∼720 g kg -1…”
Section: Discussionmentioning
confidence: 97%
“…1994;Romo et al 2000). Borsting et al (1992) indicated that triglyceride synthesis, which is an essential step for lipid absorption in the epithelial cell of the small intestine, is positively related to the degree of unsaturation of FA. Wu et al (1991) attributed the higher digestibility of unsaturated FA to their higher hydrophilic nature as the degree of unsaturation increases.…”
Section: Intakes and Flows Of Famentioning
confidence: 99%
“…Unsaturated fatty acids are known to solubilise Ca soaps [21,22] and to improve digestibility of all fatty acids [23].…”
Section: Effects Of Lecithins On Digestion Of Fatty Acidsmentioning
confidence: 99%